Application of Methods in Islamic Learning According to Imam Al-Ghazali - Riswanda (Insight School Academy, 2026)
Introduction to the Problem: Education is a very important component in human life and has become a topic of discussion among scholars, one of whom is Imam Al-Ghazali. Purpose: This research aims to gain a comprehensive understanding and analysis of the application of methods in Islamic learning according to Imam Al-Ghazali. Design/Methods/Approach: This research method uses a literature review, which means that the argumentation and reasoning used in it contain several ideas and propositions related to the study, all of which are supported by data and information obtained from literary sources. The study employs a qualitative approach with a descriptive-analytical method. Findings: This study focuses on Al-Ghazali's learning method concepts and emphasizes the importance of Islamic education. Al-Ghazali's educational approach is holistic, covering intellectual, spiritual, and moral dimensions, with the ultimate goal of forming individuals who are not only intelligent but also righteous. He emphasizes the balance between worldly and religious knowledge, the teacher's role as a role model, and instruction adapted to children's developmental stages. Research Implications/Limitations: Al-Ghazali's educational methods have implications for modern educational practice, though this study is limited to a literature review approach. Originality/Value: This study provides a thorough understanding and analysis of Al-Ghazali's thinking on the concept and approach of Islamic education and its implementation in modern educational practice.